The macro-fibre composite-bonded effect analysis on the micro-energy harvester performance and structural health-monitoring system of woven kenaf turbine blade for vertical axis wind turbine application - Ariffin, Ahmad Hamdan; Mustapha, Faizal; Hameed Sultan, Mohamed Thariq (Sage Publications, 2018)
The application of vertical axis wind turbine is suitable in a low wind speed environment. Nevertheless, vertical axis wind turbine with kenaf turbine blade will promote an additional green concept by utilising biocomposite materials. The innovation in turbine blade via macro-fibre composite as structural health–monitoring system and micro-energy harvester can enhance the vertical axis wind turbine technology application. Hence, this research’s objective is to evaluate the factors influencing the performance of micro-energy harvester and to assess the feasibility of structural health–monitoring application in biocomposite turbine blade. There are two methods to attach the macro-fibre composite used in this study, which are surface bonded and embedding into the turbine blade. Vibration simulation experiment and modal testing approach are conducted on the kenaf turbine blade, and further analysis was performed via the Taguchi statistical analysis to determine the factors affecting the micro-energy harvester and structural health–monitoring performance. The results show that by bonded to the surface as proposed is the best technique in promoting higher micro-energy harvesting at the vibration range of 10–90 Hz. Furthermore, the structural health–monitoring system was proved to operate simultaneously with the micro-energy harvesting system in turbine blades.